Pattern of Use and Dependence on Video Games in Infancy and Adolescence - Chóliz, Mariano; Marco, Clara (Anales de Psicología / Annals of Psychology, 2011)
Video games are one of the most attractive forms of leisure. Today it is one of the main activities of children and adolescents, because of the interest they have for them and the time the adolescents spend in playing. Despite the undoubted benefits of this activity, in some cases the excessive use leads to abuse and other causes serious personal and family problems. This paper has two objectives. First, analyze the pattern of use of video games, focusing on gender differences. Second, the development of a questionnaire of video games dependence, according to the criteria of DSM-IV Disorders Substance Abuse and adapting to the use of video games. The factorial structure of this questionnaire is consistent with the concept of dependence, as defined in DSM-IV. Along with Internet and mobile, video game dependency would be one of the most characteristic technological addictions.